2021
DOI: 10.3389/fpsyg.2021.648383
|View full text |Cite|
|
Sign up to set email alerts
|

Meaning-Centered Coping in the Era of COVID-19: Direct and Moderating Effects on Depression, Anxiety, and Stress

Abstract: The COVID-19 pandemic has subjected most of the world’s population to unprecedented situations, like national lockdowns, health hazards, social isolation and economic harm. Such a scenario calls for urgent measures not only to palliate it but also, to better cope with it. According to existential positive psychology, well-being does not simply represent a lack of stress and negative emotions but highlights their importance by incorporating an adaptive relationship with them. Thus, suffering can be mitigated (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 72 publications
2
53
0
1
Order By: Relevance
“…Thus, our findings are consistent with this theory on meaning-centered coping mediating the negative influence of psychological distress on perceived physical health. Our results are also in accordance with other studies, which indicate that during adverse life events meaning-centered coping can integrate cognitive, emotional, behavioral, personal and interpersonal elements that could influence subjective well-being with a sequential positive impact on the perception of physical health despite the presence of psychological distress (Wong, 2012;Van Tongeren et al, 2016;Eisenbeck et al, 2021;Jans-Beken and Wong, 2021). In light of this, coping strategies aimed to promote and sustain meaning in life definitely require more attention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our findings are consistent with this theory on meaning-centered coping mediating the negative influence of psychological distress on perceived physical health. Our results are also in accordance with other studies, which indicate that during adverse life events meaning-centered coping can integrate cognitive, emotional, behavioral, personal and interpersonal elements that could influence subjective well-being with a sequential positive impact on the perception of physical health despite the presence of psychological distress (Wong, 2012;Van Tongeren et al, 2016;Eisenbeck et al, 2021;Jans-Beken and Wong, 2021). In light of this, coping strategies aimed to promote and sustain meaning in life definitely require more attention.…”
Section: Discussionsupporting
confidence: 92%
“…We used the meaning-centered coping scale (MCCS) recently developed by Eisenbeck et al (2021) to measure meaning-centered coping during the current pandemic. Items describe coping strategies such as positive reframing, maintaining life appreciation and hope, adopting a courageous attitude against adversity, and being involved in prosocial and meaningful activities.…”
Section: Well-being Perceived Physical Health and Lonelinessmentioning
confidence: 99%
“…This harmony-based happiness can be achieved by mental toughness, responsibility (toward oneself and others), life appreciation, mindfulness, meaning in life, and the belief in a better future, which can be cultivated regardless of personal circumstances . In an ongoing international project, we have observed that such strategies play a central role in effective coping with the COVID-19 pandemic (Eisenbeck et al, 2021). Mature happiness can be considered as the mental state by-product of this dialectic way of coping with life demands.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, it is of utmost importance to identify psychological strengths that can help individuals overcome depression, stress, and anxiety and maintain well-being. Researchers have confirmed that meaning in life (Arslan et al, 2020a;Carreno et al, 2021;Eisenbeck et al, 2021), hope , positivity (Yıldırım and Güler, 2021), and self-efficacy (Yıldırım and Güler, 2020) positively influence mental health and well-being. They also identified two variables that cover dynamics in coping with adverse situations and relate to mental health and well-being.…”
Section: Introductionmentioning
confidence: 95%